PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014) - Sarnova "; Mariati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this research is to know and analyze the leverage, profitability and value of company and to know and analyze the influence of leverage and profitability to company value at manufacturing company of chemical sub sector listed in Indonesian Stock Exchange period 2010-2014 period. The data analysis technique uses financial analysis reports and statistical analysis. The population in this study is manufacturing companies in the chemical sub-sector listed on the Indonesia Stock Exchange in 2010, 2011, 2012, 2013 and 2014. Sampling technique taken from nonprobability sampling is purposive sampling. Technique of collecting data and information by using documentary data collection technique. The results showed that the leverage (Debt to Equity Ratio) at chemical manufacturing sub-company listed on Indonesia Stock Exchange 2010-2014 period is in good condition while profitability (Return on Equity) at manufacturing company of chemical sub sector listed in Indonesia Stock Exchange 2010-2014 period is not so good. Based on statistical analysis, it is found that leverage (Debt to Equity Ratio) and profitability (Return on Equity) have significant influence either partially or simultaneously to firm value (Price Book Value). Keywords: debt to equity ratio, return on equity, price book value